Meningitis for Streptococcus salivarius secondary to paradoxical cerebrospinal fluid rhinorrhea as a complication of retrosigmoid approach - Vargas Osorio, María; Muñoz Montoya, Juan; Charry Lopez, Marco; Rojas Romero, Luis (Asian Journal of Neurosurgery, 2019)
Rhinorrhea secondary to a retrosigmoid approach is rare, but when it manifests, it is due to a paradoxical cerebrospinal fluid (CSF) leak, as a result of the communication between the mastoid cells, middle ear, and eustachian tube, which finally ends on the release of CSF through the nasopharynx. Abnormal communications increases the risk of infections, not only at the surgical site but also through an ascending path. Magnetic resonance cisternography (MRC) with intrathecal gadolinium injection through a lumbar puncture not only allows an adequate diagnosis but also helps to establish management plans. Here, we present an eighty-three-year-old female patient, with a history of trigeminal neuralgia, who underwent retrosigmoid approach to perform trigeminal microvascular decompression. After intervention, the patient consulted for rhinorrhea, fever, and headache. Lumbar puncture was performed, resulting on the isolation of Streptococcus salivarius in CSF. Nuclear MRC with intrathecal gadolinium injection was performed, identifying a paradoxical CSF leak. Failure in medical management with conservative treatment ends in surgical reexploration, identifying a bone defect in mastoid cells, which was corrected.
Keywords: Nuclear magnetic resonance cisternography; paradoxical cerebrospinal fluid rhinorrhea; retrosigmoid approach; Streptococcus salivarius